Impacts of dilution on hydrogen combustion characteristics and nox emissions - Resende, Pedro (2017)
Combustion characteristics at small scales have been studied continuously due to the potential applications in portable power devices. It is known that heat release impacts at small scales result in different flame behavior as compared to conventional scales. The impacts of geometry, stoichiometry, flow rates, wall temperatures, etc. are widely studied in literature. However, dilution impacts still need to be further studied due to its important role on controlling the flame behavior and subsequent pollutants emissions at these scales. In this work, premixed hydrogen/air combustion is simulated at an axis-symmetric micro channel (with diameter D = 0:8mm and length L = 10mm), where detailed chemical kinetics are implemented in simulations (32 species and 173 reactions). The heat transfer on the wall is considered by imposing a hyperbolic temperature profile on the wall, where the wall temperature increases from 300 K at the inlet to 1300 K at the outlet. With this setup, a range of equivalence ratios including a typical fuel-lean regime (Φ= 0:7), stoichiometric regime (Φ= 1:0) and and two cases at an ultra-rich regime (Φ= 2:0 and Φ= 3:0) are investigated. For each equivalence ratio, excess dilution (using N2) is introduced to the mixture and its impact is compared with other cases. With that, the impacts of dilution variations on the combustion characteristics of premixed hydrogen/air are investigated for different equiva lence ratios. More specifically, several incidents such as flame dynamics, flame stabilization, extinctions and NOx emissions are studied for the aforementioned operating conditions.